Disease burden and medical cost-analysis of Acute Respiratory Infections in a low-income district of Bogota (2016)
Objective To estimate the burden of disease and related direct medical cost of Acute Respiratory Infections (ARI) for the health-care system in a low-income district of Bogota, generated by children under age five and senior population over age sixty.Methods A cross-sectional, retrospective, patient level study was conducted in San Cristobal district from 2008 to 2012 among the subsidized population. All inpatients and outpatients with ARI from three hospitals were reported. The total and average direct medical costs were estimated and are reported in International Dollars (Int$).Results It is estimated that, for children, ambulatory incidence rate for ARI varied between 54.4 % and 66.3 % and hospitalization rate between 9.2 % and 12.3 %. The mortality rate in the district oscillated between 18.1 and 27.7 deaths per 100000. The main medical costs where attributed to hospitalizations, and the total medical hospitalization cost per year estimated ranged between Int$ 1,334,352 and Int$ 2,139,597. In the case of senior population, the ambulatory incidence rate fluctuated between 7.6 % and 10.0 %, and the hospitalization rates between 0.6 % and 2.1 %; the mortality rate ranged between 8.9 and 47.8 deaths per 100.000. Hospitalization cost per year was estimated to be between Int$ 88,957 and Int$ 373,382.Conclusion Direct medical costs due to ARI have an important disease and direct medical cost burden in this low-income district.